Optimization of filtered neutron beams for the calibration of superheated droplet detectors at the RPI - Nascimento, F. (2007)
Superheated droplet detectors (SDDs) have been investigated for applications in neutron dosimetry and spectrometry. Varying the detector temperature, it is possible to change the neutron energy detection threshold of SDDs, thus allowing the use of a single detector to measure neutrons of different energy, without any change of the experimental setup. However, the neutron threshold energy versus temperature curves have to be experimentally determined. The determination of the calibration curves requires the use of monochromatic neutron beams.